Global medicinal uses of Euphorbia L. (Euphorbiaceae). (24th December 2015) - Ernst, Madeleine; Grace, Olwen M.; Saslis-Lagoudakis, C. Haris; Nilsson, Niclas; Simonsen, Henrik Toft; Rønsted, Nina
Abstract: Ethnopharmacological relevance: The genus Euphorbia (spurges, Euphorbiaceae) is the third largest genus of flowering plants, with almost 2000 species. Its exceptional diversity of growth forms and near-cosmopolitan distribution have attracted human interest since ancient times. For instance in Australia, topical application of latex of Euphorbia peplus L. is used as a home treatment for skin cancer and actinic keratosis. Its use in Australian folk medicine has inspired the release of the drug Picato® (ingenol mebutate), and further fostered interest in natural products and medicinal uses of Euphorbia in recent years. Aim of the study: To provide an indicative overview of medicinal uses of the genus Euphorbia driven by the recent interest in biologically active natural products from Euphorbia in drug discovery. We assess documented medicinal knowledge and value of the genus Euphorbia and the taxonomic distribution of this value. Materials and methods: We undertook an extensive survey of over 260 multidisciplinary publications on the online repository JSTOR using the search term " Euphorbia medicinal". Results: Medicinal uses were identified for >5% of the species in the genus, including descriptions of treatments for a variety of diseases. The most-cited medicinal uses around the world were treatments for digestive system disorders, skin ailments and, especially in the Southern hemisphere, infections. Consensus ratios indicated that the most-valued medicinal uses of Euphorbia species are in the treatment of digestive and respiratory complaints, inflammation and injuries, especially by members of Euphorbia subg. Chamaesyce. Conclusions: The present study gives a first indicative overview of Euphorbia species used for health and wellbeing around the world. The exceptional diversity of the genus Euphorbia is not only represented by its growth forms but also by its diverse medicinal uses. Our results highlight the importance of research into medicinal uses of Euphorbia species and their importance as a source of natural products. Furthermore the medicinally highly valuable subgenus Chamaesyce was identified as chemically under-investigated, emphasizing the need for further studies investigating the chemical diversity to which the high medicinal value of Euphorbia subg. Chamaesyce can be attributed. Graphical abstract: